199k views
0 votes
Find the 6th term in the sequence defined by d(n) = 8 - 6(n - 1).

A. 2
B. 8
C. -26
D. -38

1 Answer

3 votes

Final answer:

The 6th term in the sequence defined by d(n) = 8 - 6(n - 1) is -22.

Step-by-step explanation:

To find the 6th term in the sequence defined by d(n) = 8 - 6(n - 1), we need to plug in the value of n into the equation and simplify.

  1. Substitute n = 6 into the equation: d(6) = 8 - 6(6 - 1)
  2. Simplify the expression within the parentheses: d(6) = 8 - 6(5)
  3. Perform the multiplication: d(6) = 8 - 30
  4. Subtract: d(6) = -22

The 6th term in the sequence is -22, which corresponds to option C.

User Brittni
by
7.1k points